Specialization directs habitat selection responses to a top predator in semiaquatic but not aquatic taxa - Šigutová, Hana; Harabiš, Filip; Šigut, Martin; Vojar, Jiří; Choleva, Lukáš; Dolný, Aleš (Scientific reports, 2021)
Habitat selectivity has become an increasingly acknowledged mechanism shaping the structure of freshwater communities; however, most studies have focused on the effect of predators and competitors, neglecting habitat complexity and specialization. In this study, we examined the habitat selection of semiaquatic (amphibians: Bufonidae; odonates: Libellulidae) and aquatic organisms (true bugs: Notonectidae; diving beetles: Dytiscidae). From each family, we selected one habitat generalist species able to coexist with fish (Bufo bufo, Sympetrum sanguineum, Notonecta glauca, Dytiscus marginalis) and one species specialized in fishless habitats (Bufotes viridis, Sympetrum danae, Notonecta obliqua, Acilius sulcatus). In a mesocosm experiment, we quantified habitat selection decisions in response to the non-consumptive presence of fish (Carassius auratus) and vegetation structure mimicking different successional stages of aquatic habitats (no macrophytes; submerged and floating macrophytes; submerged, floating, and littoral-emergent macrophytes). No congruence between habitat specialists and generalists was observed, but a similar response to fish and vegetation structure defined both semiaquatic and aquatic organisms. While semiaquatic generalists did not distinguish between fish and fishless pools, specialists avoided fish-occupied pools and had a preferred vegetation structure. In aquatic taxa, predator presence affected habitat selection only in combination with vegetation structure, and all species preferred fishless pools with floating and submerged macrophytes. Fish presence triggered avoidance only in the generalist bug N. glauca. Our results highlight the significance of habitat selectivity for structuring freshwater ecosystems and illustrate how habitat selection responses to a top predator are dictated by specialization and life history.
Keywords: Animals; ropuchy; Food Chain; Coleoptera; Herbivory; Odonata; brouci; Fishes; Predatory Behavior; Animal Distribution; ryby; Fresh Water; vážky; sladká voda; býložravci; predátorské chování; zvířata; potravní řetězec; rozšíření zvířat; Bufonidae